Thermal transport studies on charge density wave materials LaPt2Si2 and PrPt2Si2. (2nd November 2018) - Gupta, Ritu; Rajeev, K P; Hossain, Z
Abstract: We measured the thermal properties of polycrystalline samples of LaPt2 Si2 and PrPt2 Si2 using thermopower ( S ) along with thermal conductivity ( κ ) in the temperature range 10 K–300 K. Significant anomalies related to charge density waves (CDW) around 112 K and 88 K respectively have been observed in in both systems. Analysis of thermopower by a two band model suggests that the observations are consistent with a reduction of electron charge density. A change in slope accompanied by a drop in the value of thermal conductivity has been observed around T CDW in case of LaPt2 Si2 . Analysis of thermal conductivity of this material suggests that the CDW mainly affects electronic contribution to thermal transport. Only a slight change of slope has been detected in temperature dependent thermal conductivity in the case of PrPt2 Si2 around T CDW, while its resistivity shows a clear anomaly which shows that electronic part of thermal conductivity is mainly influenced by the CDW in this case also. It is interesting to note that the lattice contribution to thermal conductivity remains unaffected by the CDWs in both materials.